2016
DOI: 10.1016/j.yebeh.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the burden of idiopathic generalized epilepsy in the United States, Europe, and Brazil: An analysis from the National Health and Wellness Survey

Abstract: The aim of this study was to understand the current burden of primary generalized tonic-clonic seizures (PGTCS) associated with idiopathic generalized epilepsy (IGE) as a function of seizure frequency. We analyzed data for (IGE) as a proxy measure of PGTCS. Little is known about the quality of life (QoL), health utility, productivity, healthcare resource utilization (HRU), and cost burden of PGTCS or IGE. Patients were identified from the US (2011, 2012, & 2013), 5EU (2011 & 2013), and Brazil (2011 & 2012) Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Increased seizure frequency is exactly associated with worse outcomes and the burdens of epilepsy. Of course, new antiepileptic drugs (AEDs) may reduce these adverse events and can improve the prognosis of patients with epilepsy [5]. However, the existing AEDs fail to prevent or cure the 20-30% of epileptic patients [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Increased seizure frequency is exactly associated with worse outcomes and the burdens of epilepsy. Of course, new antiepileptic drugs (AEDs) may reduce these adverse events and can improve the prognosis of patients with epilepsy [5]. However, the existing AEDs fail to prevent or cure the 20-30% of epileptic patients [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Additional stratifications for race/ethnicity distributions were performed for the United States. Additional details regarding data collection and sampling procedures are available from a similar companion study for idiopathic generalized epilepsy . The NHWS study protocol was approved by Essex IRB (Lebanon, NJ, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this variable, another indirect cost variable that factored in unemployment as 100% absenteeism was created for patients ages 18–60. Further details on these measures, patient demographics, health characteristics, health outcomes, and costing methods are available in the companion study publication …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis found that IGE patients demonstrated significantly lower scores on tests across all cognitive factor-domains except visual-spatial abilities [3] and increasing seizure frequency was significantly associated with worse outcomes [19]. Epilepsy is not understood as a disorder affecting one discrete brain region but as a disorder of widespread brain networks [20].…”
Section: Introductionmentioning
confidence: 99%